Analysing Devotees' Compliance and Health Protocols on Religious Worship During Pandemic Covid-19 In Indonesia - Yulita T. Retanubun; Moses Glorino. Rumambo Pandin; Maria Ardiiningsih Pandin (Qubahan Academic Journal)
The study aims to determine the picture of community compliance in complying with health protocols in places of worship during the COVID-19 pandemic. The method used in this study is quantitative research, with the design used being descriptive analysis and questionnaires and interviews as a tool for conducting research. The total sample in quantitative research was 30, with 15 respondents selected to be interviewed. The results found respondents in adulthood were more compliant with the application of health protocols and based on attitudes in respondents who had a high level of confidence in information could affect religious devotees’ adherence in complying with health protocols. The recommendation of the study are socialization and education from religious leaders, health workers, and community leaders, periodically, can still be done orally or in writing and can be done to increase knowledge for religious devotees to comply with health protocols following the policies of the central government. The limitation of the samples can be increased more than one place, so it can be involved religious devotees when they are performing worship.